DETERMINAN VOLATILITAS HARGA SAHAM PADA INDEKS IDX30 (STUDI PADA TAHUN 2018-2021) - Atalia Putri Ramadhan; Ferry Prasetyia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The purpose of this study is to determine the factors that influence the volatility of the IDX30 company’s stock prices. Independent variable used are Stock Trading Volume, dividend policy, leverage, firms size, and asset growth. This study using the report data from companies listed in IDX in the Index IDX30 between 2018-2021. Data analyzed using data panel regression analysis. The result from the analysis found out if variable dividend yield, firm size, and growth asset has no significant effects on Stock Price Volatility. Meanwhile, trading volume and leverage have a significant effect on stock price volatility.